Determinan Minat Beli Asuransi Jiwa Syariah Pada Kalangan Generasi Milenial Di Kota Surakarta - Kamelya Azzahra; Mufti Arief Arfiansyah (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
Sharia compliant life insurance stands out as a really great way to handle your money. It is seen as very valuable because it fits with the sharia law rules and pushes the idea of those in the insurance plan supporting one another. However, the community looks at some important things when trying to get millennials in Surakarta City more keen on purchasing sharia life insurance choices. The things that were looked at are how big the contribution amounts are, what good things the insurance covers, how it is promoted, understanding what it is, and everyone's thoughts when considering how interested they might be. The main focus of this study is on purchase intent, which is seen as the thing being impacted. This research uses a numerical method, with information gathered from surveying 100 millennials between 30 and 44 years old in Surakarta City, chosen through a method that picks people randomly. The data was processed and checked using SPSS 25 software for running tests. The samples were checked to see if they measure things properly and how consistent they are by using tests to check for validity and reliability. After this, some linear regression analyses are done, along with tests to make sure standard statistical assumptions are correct, separate assessments (t-tests), combined evaluations (F-tests), and numbers showing how well the model fits the data. The study's findings show that fund contributions and personal opinions affect whether they plan to buy. In the meantime, insurance payouts, job advancement, and understanding products don't have much impact on their own. But all the different things together do change how likely people are to buy Sharia life insurance. This work should help with making good marketing plans for Sharia life insurance businesses that fit with Sharia beliefs and rules. The main aim here is to see what makes young adults in Surakarta think about getting Sharia life insurance.